2017
DOI: 10.7860/jcdr/2017/24278.9213
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B-Induced Diffuse Cutaneous Hyperpigmentation

Abstract: We present a rare case of Polymyxin B-induced diffused cutaneous skin hyperpigmentation in a 65-year-old elderly male of Indian origin. This patient had initially presented in the emergency with shortness of breath and low grade intermittent fever for last three months. He was also suffering from persistent productive cough and occasional haemoptysis for same duration. He was a known case of Chronic Obstructive Pulmonary Disease (COPD) for last 3 years and was on oral and inhalational medications.No past histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…PMB‐iH has been reported in the pediatric population, likely due to slower renal‐drug clearance rate in younger patients, which results in higher drug levels 5 . Presumably, patients who have renal‐insufficiency would be at more risk of developing PMB0‐iH 6 . However, this is unlikely an exacerbating factor of PMB‐iH in our patient due to her normal renal function post‐transplant.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…PMB‐iH has been reported in the pediatric population, likely due to slower renal‐drug clearance rate in younger patients, which results in higher drug levels 5 . Presumably, patients who have renal‐insufficiency would be at more risk of developing PMB0‐iH 6 . However, this is unlikely an exacerbating factor of PMB‐iH in our patient due to her normal renal function post‐transplant.…”
Section: Discussionmentioning
confidence: 66%
“…More men and darker‐skinned patients (Fitzpatrick scale IV as opposed to I‐III) are affected (Table 1). 3,7‐9 Although some patients developed diffuse hyperpigmentation, 10 others had limited skin discoloration to photo‐exposed areas such as the face and neck 6,8 . According to a recent cohort study of 60 patients with gram‐negative infection who received 14‐day course of PMB, hyperpigmentation was observed by the 3rd day of treatment and improved gradually upon medication discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…et al reported two suspected cases in 2007 for the first time [ 7 ]. A patient who suffered from MDR-KP infection was found with SH after treated by intravenous PMB for 4 days, according to the description by Lahiry S. et al [ 8 ]. Besides, there were several cases in neonates and infants as well.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Isolated cases of hyperpigmentation due to levofloxacin have been described, although in isolated cases and long-term treatment regimens, or due to polymyxin, an antibiotic used primarily for resistance against Gram-negative germs, or to tigecycline, a new glycylcycline antibiotic. [13][14][15][16] .…”
Section: Antibioticsmentioning
confidence: 99%